Embedded real time blink detection system with heart rate sensing for driver fatigue monitoring - Habiba, Umme Saira; Ahmed, Shafinaz Nadia; Angkan, Prithila; Sahad, Md Arman Noor (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.